A new genus, Duffelsa gen. n., with descriptions of three new species and one new combination (Hemiptera: Cicadidae) - Wang, Jiali; Jiang, Jinyuan; Wei, Cong (Zootaxa, 2023)
One new cicada genus, Duffelsa gen. n., is erected in the tribe Leptopsaltriini Moulton, 1923, with the designation of Pomponia orientalis (Distant, 1912) as the type species. Three new species, D. parvula sp. n., D. grandia sp. n. and D. rubida sp. n., are described from China. A key to species of Duffelsa gen. n. is provided. The relationship of this new genus to related taxa is discussed.